Comparison of airway pressures and expired gas washout for nasal high flow versus CPAP in child airway replicas - Kelvin Duong (BMC, 2021)
Abstract Background For children and adults, the standard treatment for obstructive sleep apnea is the delivery of continuous positive airway pressure (CPAP). Though effective, CPAP masks can be uncomfortable to patients, contributing to adherence concerns. Recently, nasal high flow (NHF) therapy has been investigated as an alternative, especially in CPAP-intolerant children. The present study aimed to compare and contrast the positive airway pressures and expired gas washout generated by NHF versus CPAP in child nasal airway replicas. Methods NHF therapy was investigated at a flow rate of 20 L/min and compared to CPAP at 5 cmH2O and 10 cmH2O for 10 nasal airway replicas, built from computed tomography scans of children aged 4–8 years. NHF was delivered with three different high flow nasal cannula models provided by the same manufacturer, and CPAP was delivered with a sealed nasal mask. Tidal breathing through each replica was imposed using a lung simulator, and airway pressure at the trachea was recorded over time. For expired gas washout measurements, carbon dioxide was injected at the lung simulator, and end-tidal carbon dioxide (EtCO2) was measured at the trachea. Changes in EtCO2 compared to baseline values (no intervention) were assessed. Results NHF therapy generated an average positive end-expiratory pressure (PEEP) of 5.17 ± 2.09 cmH2O (mean ± SD, n = 10), similar to PEEP of 4.95 ± 0.03 cmH2O generated by nominally 5 cmH2O CPAP. Variation in tracheal pressure was higher between airway replicas for NHF compared to CPAP. EtCO2 decreased from baseline during administration of NHF, whereas it increased during CPAP. No statistical difference in tracheal pressure nor EtCO2 was found between the three high flow nasal cannulas. Conclusion In child airway replicas, NHF at 20 L/min generated average PEEP similar to CPAP at 5 cm H2O. Variation in tracheal pressure was higher between airway replicas for NHF than for CPAP. The delivery of NHF yielded expired gas washout, whereas CPAP impeded expired gas washout due to the increased dead space of the sealed mask.